Two‐Dimensional Supramolecular Electron Spin Arrays (Adv. Mater. 17/2013). (2nd May 2013) - Wäckerlin, Christian; Nowakowski, Jan; Liu, Shi‐Xia; Jaggi, Michael; Siewert, Dorota; Girovsky, Jan; Shchyrba, Aneliia; Hählen, Tatjana; Kleibert, Armin; Oppeneer, Peter M.; Nolting, Frithjof; Decurtins, Silvio; et al.
<x xml:space="preserve">Abstract</x> Addressable arrangements of spins at the molecular scale provide novel and exciting possibilities towards future spintronic applications. On page 2404, Nirmalya Ballav, Christian Wäckerlin, and co‐workers employ a bottom‐up approach to build a two‐dimensional array containing paramagnetic Mn and Fe complexes arranged in a chessboard‐like lattice. On‐surface magnetochemistry allows for the selective switching of this spin array. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>